2016
DOI: 10.1002/hbm.23368
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis on the neural basis of planning: Activation likelihood estimation of functional brain imaging results in the Tower of London task

Abstract: The ability to mentally design and evaluate series of future actions has often been studied in terms of planning abilities, commonly using well-structured laboratory tasks like the Tower of London (ToL). Despite a wealth of studies, findings on the specific localization of planning processes within prefrontal cortex (PFC) and on the hemispheric lateralization are equivocal. Here, we address this issue by integrating evidence from two different sources of data: First, we provide a systematic overview of the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 91 publications
(213 reference statements)
3
42
0
4
Order By: Relevance
“…Previous studies have reported that PFC has a critical role during cognitive planning (Kirsch et al, 2006;Newman, Carpenter, Varma, & Just, 2003;Owen et al, 1996;Nitschke et al, 2017) and the present results show that cognitive planning induces a FMθ activity (Figures 4-8) originating in PFC, specifically SF and ACC (Figure 9). These results are in line with previous studies on higher order cognitive functions (Cavanagh & Frank, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have reported that PFC has a critical role during cognitive planning (Kirsch et al, 2006;Newman, Carpenter, Varma, & Just, 2003;Owen et al, 1996;Nitschke et al, 2017) and the present results show that cognitive planning induces a FMθ activity (Figures 4-8) originating in PFC, specifically SF and ACC (Figure 9). These results are in line with previous studies on higher order cognitive functions (Cavanagh & Frank, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…Neuroimaging studies have provided valuable evidence about the critical role of the prefrontal cortex (PFC) in cognitive control, including planning. The most traditional paradigm used in those studies to evaluate planning is the Tower of London Task (TOL) (Shallice, 1982;Unterrainer et al, 2004) which suggested an important implication of the dorsolateral PFC (DLPFC) (Nitschke et al, 2017), the dorsal anterior cingulate cortex (dACC) and the superior parietal lobe (SPL), among other brain regions (Kirsch et al, 2006;Newman, Carpenter, Varma, & Just, 2003;Owen, Doyon, Petrides & Evans, 1996). Besides TOL, there are others traditional tests that measure planning: Porteus (1959) proposed the Porteus Maze Task which has been widely used to study planning skills in a PFC-dependent visuospatial context in healthy control and neuropsychiatric population (Gallhofer, Bauer, Lis, Krieger, & Gruppe, 1996;Krieger, Lis, & Gallhofer, 2001;Lee, Chou, Li, Wan, & Yen, 2007;Lezak, 1995;Peters & Jones, 1951;Tremblay et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Writing per se activates a large network of regions, including the bilateral BA 9 of the prefrontal cortex, thalamus, cerebellum and bilateral parietal and left temporal areas (Yuan & Brown, 2015). The dorsolateral prefrontal cortex (BA 9 and 46) has been linked to executive functions, such as working memory and planning processes in complex cognitive tasks (e.g., Nitschke, Köstering, Finkel, Weiller, & Kaller, 2017). In the context of language processing, the left BA 9 was active during idiomatic sentence processing that requires additional resources compared to literal language processing (Lauro, Tettamanti, Cappa, & Papagno, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cognitive planning is considered as a function subserved by the dorsolateral frontal cortex (Beauchamp, Dagher, Aston, & Doyon, ; Newman, Carpenter, Varma, & Just, ; Nitschke, Kostering, Finkel, Weiller, & Kaller, ; Schall et al, ; Wagner, Koch, Reichenbach, Sauer, & Schlosser, ). The Tower of London task (Shallice, ) is widely used to investigate the cognitive planning ability, which requires participants to imagine a complex sequence of steps to move blocks from one position to another under specific constraints.…”
Section: Introductionmentioning
confidence: 99%